A novel simplified ultra-rapid freezing technique for cryopreservation of tissue slices - Rypka, Miroslav; Červenková, Kateřina; Uherková, Lenka; Poczatková, Hana; Florschutz, Antony V; Veselý, Jaroslav (Cryobiology, 2006)
Cryopreservation offers the potential to maximize the use and availability of biological materials that have a limited supply. This study demonstrates an enhanced technique for the parallel cryopreservation of a series of liver tissue slices using a tray modeled from aluminium foil and low concentrations of a cryoprotectant. Cooling and warming rates of approximately 2000 and 3900 degrees C min(-1), respectively, were achieved as the thermal capacity of the foil-tray was significantly reduced compared to the aluminium sandwich device introduced by Day et al. [S.H. Day, D.A. Nicoll-Griffith, J.M. Silva, Cryopreservation of rat and human liver slices by rapid freezing, Cryobiology 38 (1999) 154-159]. Additionally, the two critical steps involved in the sandwich approach, i.e., clamping the plates and complete filling of the entire space between the plates with liquid, can be omitted using the foil tray. The viability of the slices was verified by measuring tetrazolium salt reduction capacity, cytosolic enzyme lactate dehydrogenase leakage, and ethoxycoumarin metabolism.
Keywords: Liver; financování organizované; Animals; Cryopreservation; játra; tetrazoliové soli; umbeliferony; Thiazoles; thiazoly; Time Factors; časové faktory; Freezing; Mice; Tetrazolium Salts; Umbelliferones; myši; kryoprezervace; Financing, Organized; uchovávání orgánů; L-Lactate Dehydrogenase; Male; L-laktátdehydrogenasa; Cell Survival; Organ Preservation; zmrazování; zvířata; viabilita buněk; mužské pohlaví